How to live in a post-meltdown and -spectre world. - Bennett, Rich; Callahan, Craig; Jones, Stacy; Levine, Matt; Miller, Merrill; Ozment, Andy (Communications of the ACM, 2018)
Learn from the past to prepare for the next battle.